2021
DOI: 10.3892/mmr.2021.12025
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑1271‑5p alleviates the malignant development of hepatitis B virus‑mediated liver cancer via binding to AQP5

Abstract: Hepatitis B virus (HBV) is a leading cause of liver-related cancer. Progress has been made on the study of microRNA (miRNA or miR) function in HBV-related liver cancer. Hence, the objective of the present study was to determine the role and functional mechanism of miR-1271-5p in HBV-associated liver cancer. miR-1271-5p and aquaporin 5 (AQP5) expression at the mRNA level were measured by reverse transcription-quantitative PCR (RT-qPCR). The levels of hepatitis B e-antigen (HBeAg), hepatitis B surface antigen (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…MiR‐1271‐5p contributes to the development of a variety of cancers and functions as a tumor suppressor 12–15 . The differential genes from TCGA COAD datasets and the obtained putative targets of miR‐1271‐5p were analyzed (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐1271‐5p contributes to the development of a variety of cancers and functions as a tumor suppressor 12–15 . The differential genes from TCGA COAD datasets and the obtained putative targets of miR‐1271‐5p were analyzed (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Here, FISH, a luciferase reporter assay, and RT‐qPCR analysis indicated that circCASK exerted its function by sponging miR‐1271‐5p and thus forming the circCASK/miR‐1271‐5p regulatory axis. It has been reported that miR‐1271‐5p plays an important tumor‐suppressor role in several cancers, including liver, 15 prostate, 30 endometrial, 31 ovarian, 13 cervical, 32 and lung cancer 33 . More importantly, miR‐1271‐5p suppresses CRC carcinogenesis 34 .…”
Section: Discussionmentioning
confidence: 99%
“… 42 Li et al demonstrated that overexpression of miR‐1271‐5p inhibits HBV antigens and suppresses tumor growth by reducing the expression of AQP5. 43 Tuberculosis (TB) is caused by Mycobacterium tuberculosis, which most commonly affects the lungs but can also affect any other part of the body. Diagnosis of TB is a major challenge that requires the development of accurate diagnostic tools.…”
Section: Mirna and Disease Associationmentioning
confidence: 99%
“…Li et al demonstrated higher expression of miR‐487b in serum of infected patients, thus miR‐487b can be used as a diagnostic marker for HCC 42 . Li et al demonstrated that overexpression of miR‐1271‐5p inhibits HBV antigens and suppresses tumor growth by reducing the expression of AQP5 43 . Tuberculosis (TB) is caused by Mycobacterium tuberculosis, which most commonly affects the lungs but can also affect any other part of the body.…”
Section: Mirna and Disease Associationmentioning
confidence: 99%
“…Li et al confirmed that silencing miRNA-210 can inhibit HepG2 by up-regulating EGR3 to promote apoptosis ( Li X. et al, 2020 ). In tissues with HBV-associated HCC, miR-1271-5p was down-regulated and AQP5 was up-regulated ( Li Z. et al, 2021 ). miR-122 can specifically bind to the 3′-untranslated region (3′UTR) of apolipoprotein B mRNA editing enzyme catalytic subunit 2 (APOBEC2) mRNA and inhibit its expression.…”
Section: Pathogenic Factorsmentioning
confidence: 99%